Detection of beta-lactamase production in clinical Prevotella species by MALDI-TOF MS method - ÜLGER, NURVER (ELSEVIER SCI LTD, 2020)
Penicillins, can be used in treatment of infections due to Prevotella species if they are susceptible to penicillin. Early and accurate preliminary detection of beta-lactamase-producing isolates is crucial for treatment of infection. The aim of this study was to determine beta-lactamase-producing Prevotella species by MALDI-TOF MS and screen them for the presence of cfxA gene, responsible for beta-lactamase production. A total of 500 clinically relevant Prevotella isolates, collected from 13 countries for the previous European antibiotic resistance surveillance study, were tested. Susceptibility testing was performed against ampicillin and ampicillin/sulbactam by Etest methodology. EUCAST guidelines were used for susceptibility interpretations; the isolates with MIC value 0.5 for ampicillin were considered susceptible and 2 resistant. All Prevotella isolates, were tested for detection of beta-lactamase activity by MALDI TOF MS (Vitek (R) MS Research Use Only) system and the presence of the cfxA gene by PCR method. The susceptibility levels of the isolates to ampicillin/sulbactam and ampicillin were 99.6% and 43.4%, respectively. A total 59% of isolates presented beta-lactamase activity and 60.8% were cfxA gene positive. Both these tests were positive for isolates in the resistant category. Additionally, >95% of the isolates (n = 65) which ampicillin MIC values ranged from >0.5 mu g/mL to 2 mu g/ml displayed beta-lactamase activity. We also found that the MALDI-TOF MS-based beta-lactamase assay delivers results in 2 h. We found a high concordance between the MALDI-TOF MS beta-lactamase results in terms of cfxA beta-lactamase gene presence. MALDI-TOF MS may serve as a simple and efficient alternative method of the existing phenotypic and PCR-based methods. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Anaerobic bacteria; Prevotella; beta-lactamase; cfxA gene; MALDI-TOF mass Spectrometry; VITEK MS; FLIGHT MASS-SPECTROMETRY; LASER-DESORPTION IONIZATION; BACTEROIDES-FRAGILIS STRAINS; IN-VITRO SUSCEPTIBILITIES; RAPID DETECTION; ANTIMICROBIAL SUSCEPTIBILITY; ANTIBIOTIC-RESISTANCE; TIME; BACTERIA